2010
DOI: 10.1002/pssb.200945463
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic, linear, and nonlinear optical properties of ZnCdTe2 chalcopyrite

Abstract: We report results of first-principles density functional calculations using the full-potential linearized augmented plane wave method. The generalized gradient approximation (GGA) and the Engel-Vosko-GGA (EV-GGA) formalism were used for the exchange-correlation energy to calculate the structural, electronic, linear, and nonlinear optical properties of the chalcopyrite ZnCdTe 2 compound. The valence band maximum and the conduction band minimum are located at the G-point, resulting in a direct band gap of about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The calculated band gap (1.90 eV) using mBJLDA for ZnCdTe2 is in accordance to experimental value of 1.99 eV Further, this value of band gap is far better than the value as calculated by Ouahrani et al 15 using EV-GGA i.e. 1.29 eV.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The calculated band gap (1.90 eV) using mBJLDA for ZnCdTe2 is in accordance to experimental value of 1.99 eV Further, this value of band gap is far better than the value as calculated by Ouahrani et al 15 using EV-GGA i.e. 1.29 eV.…”
Section: Resultssupporting
confidence: 87%
“…ZnxCd1-xTe alloys are the basic elements in the fabrication of the solid-state detectors for medical applications 12 and astronomical physics [13][14] . Ouahrani et al 15 used generalized gradient approximation (GGA) and Engel Vosko -GGA (EV-GGA) formalisms for the exchange correlation potentials to correct band gap of the chalcopyrite ZnCdTe2 compound and to find linear, and nonlinear optical properties. They revealed that this compound shows considerably strong birefringence as a consequence of anisotropy in optical response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the magnitude of the imaginary part of the second-order NLO susceptibility, especially in the low frequency region, would be approximately proportional to the inverse of the fourth power of the band gap. However, compared to common semiconductors with semblable band gaps, 13,[42][43][44][45][46][47][48][49] one-dimensional selenium and tellurium exhibit much larger second-order NLO responses. To further investigate the origins of the enhanced NLO effects of one-dimensional systems, we calculate the deformation charge density, as depicted in Fig.…”
Section: Bulk Photovoltaic Effect Of Se and Te Chainsmentioning
confidence: 99%
“…Various fundamental concepts and technological objectives have been investigated in different scientific areas [1]. The ternary chalcopyrite's A B X IV semiconducting spinels are attractive due to their optoelectronic, electro-optic, thermoelectric and nonlinear optical applications [4,5]. The spinel structure is composed of tetrahedral (T) and an octahedral (O) sites occupied by the cations surrounded by the X atom with the positional specifications (u, u, u) [6].…”
Section: Introductionmentioning
confidence: 99%